2009
DOI: 10.2478/s11756-009-0104-9
|View full text |Cite
|
Sign up to set email alerts
|

Agro-ecological field vulnerability evaluation and climate change impacts in Souma area (Iran), using MicroLEIS DSS

Abstract: Soil erosion and contamination are two main desertification indices or land degradation agents in agricultural areas. Global climate change consequence is a priority to predict global environmental change impacts on these degradation risks. This agro-ecological approach can be especially useful when formulating soil specific agricultural practices based on the spatial variability of soils and related resources to reverse environmental degradation. Raizal and Pantanal models within the new MicroLEIS framework, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
(1 reference statement)
0
10
0
1
Order By: Relevance
“…Land degradation is an interactive process involving multiple causal factors, among which climate variability, soil quality, and land management play a significant role (Bajocco et al 2012;Rasmy et al 2010;Shahbazi et al 2009). It reduces soil fertility and is generally associated with geophysical conditions (e.g.…”
Section: Data Processingmentioning
confidence: 99%
“…Land degradation is an interactive process involving multiple causal factors, among which climate variability, soil quality, and land management play a significant role (Bajocco et al 2012;Rasmy et al 2010;Shahbazi et al 2009). It reduces soil fertility and is generally associated with geophysical conditions (e.g.…”
Section: Data Processingmentioning
confidence: 99%
“…The soil morphological, physical and chemical characteristics of representative soil families, which will use as data input in the Almagra model, are summarized in Table 1. Climate characteristics of the study area can be found in Shahbazi et al (2009). The field work was carried out with a general reconnaissance survey through the whole study area to be familiar with the different aspects available of the area, i.e.…”
Section: This Study Was Performed In the Souma Area Between 44mentioning
confidence: 99%
“…Wheat-alfalfasoybean was selected as the best crop rotation. Also, land capability evaluation and climate change impacts in semi-arid and Mediterranean areas using MicroLEIS DSS was assessed (Shahbazi et al 2008b) and results showed that maize has 70% and 35% of yield reduction respectively in Ahar and Seville area, and this coefficient will increase 20% by climate change. Yehia (2007) used the MicroLEIS software to evaluate the soil of Bangar el-Sokkar area (Egypt) and found the dominant capability subclasses of S2l, S2tl, and S3l with soil properties and topographic conditions as main limiting factors.…”
Section: Introductionmentioning
confidence: 99%
“…An enormous technological and research effort is being carried out worldwide to predict the impact and future trends of global climate change (Gay & Estrada, 2010;Shahbazi et al, 2009;Walker & Schulze, 2008;Wigley, 2008). This knowledge is crucial for the adoption of both preventive and mitigating measures and of adaptive strategies in urban and rural environments.…”
Section: Introductionmentioning
confidence: 99%
“…En todo el mundo se está llevando a cabo un enorme esfuerzo tecnológico y de investigación para predecir el impacto y las tendencias futuras del cambio climático global (Gay & Estrada, 2010;Shahbazi et al, 2009;Walker & Schulze, 2008;Wigley, 2008). Este conocimiento es importante para la adopción de medidas preventivas y de mitigación, así como de estrategias de adaptación en ambientes urbanos y rurales.…”
Section: Introductionunclassified